ANALISIS YURIDIS PELAKSANAAN OBLIGASI KONVERSI (CONVERTIBLE PERFORMANCE DEBENTURE) PADA PT. SUBANA REKHA LESTARI Tbk. - Sri Nugrahaning Widhi, Budiharto, Yuli Prasetyo Adhi (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Convertible securities are one means to attract investors that are interested in investing in a company. The problem that is often experienced by a body of corporate law in the development of its business requires huge capital to expand its business. Companies / issuers attract investors by issuing securities such as bonds and stocks that can provide great benefits. But behind the benefits of such securities are risk differs between bonds and stocks. The process of the conversion of securities in a limited liability company requires a variety of steps that must be done and the legal consequences arising from the conversion of bonds into shares of the convertible bond agreement. Considering the conversion process involves a variety of institutions and professions that exist in the capital markets. It is therefore necessary synergy between legislation.